Attempts To Determine Differences Between Centralized and Decentralized Inter-Organizational Networks with A Focus on Leadership – Selected Research Results of Polish Business Organizations - Michał Organa (Communications of International Proceedings, 2024)
The article presents chosen results obtained during the research process focused on Polish organizations involved in inter-organizational networks. Depending on respondents' opinions, such networks were distinctly discerned as centralized or decentralized. Assuming the existence of significant differences between the functioning of the indicated types of inter-organizational networks based on the analysis of the literature on the subject, the author attempts to recognize such differences more precisely, especially in the context of the benefits achieved with particular emphasis on the influence of leadership implemented in organizations belonging to specific networks. Therefore, the motive for the conducted research is to understand better and specify the differences between centralized and decentralized networks. There is still a significant research gap in the literature on the subject in this area, especially in the context of the forms of leadership dedicated to these networks. The insufficient specification of the differences between centralized and decentralized networks justifies undertaking the research topic and gives them validity. This article aims to diagnose and characterize selected areas that differentiate the functioning of centralized and decentralized inter-organizational networks based on the results of the research conducted on organizations declaring their belonging to a specific type of the considered networks. In addition, the author focuses on determining the nature of the leadership influence implemented in the networks, which is one of the potential key differences in the scope mentioned above. The selection of the study respondents was purposeful and followed the availability rule. Ultimately, a research sample of 102 respondents was obtained, representing Polish organizations belonging to centralized networks (51 people) and decentralized networks (also 51 people). The study was conducted using the CATI (Computer Assisted Telephone Interviewing) method based on an original survey form. Based on the research frame used and the respondents' answers, it can be assumed that there are differences, but their detailed confirmation requires additional analyses, primarily using statistical methods. Differences between centralized and decentralized networks were observed, especially in the following areas: motives for joining the chosen network system, perception of benefits from participating in a network, and leadership influence perception within the considered networks. The presented results are preliminary analyses and will be developed in subsequent publications.
Keywords: comparison of centralized and decentralized networks; network leadership